Driving force of rising renewable energy in China: Environment, regulation and employment. (February 2017) - Zhao, Xu; Luo, Dongkun
Abstract: This paper studies the development of renewable energy in China by examining the driving force of environment quality, regulation and employment on renewable energy generation. We adopt renewable energy as a metric for environment quality, and test the relationship between renewable energy and income using Environment Kuznets Curve (EKC) theories. The impact of employment on renewable energy is tested, and dummy variables are used to indicate when the regulation was in effect. The results show that there exists a quadratic relationship between renewable energy and income. But the results fail to provide that the renewable energy generation is a job creator when the lagged unemployment rate is included as an explaining variable. We consider the employment population, and the finding shows that the employment can promote the development of renewable energy. The regulation has significantly positive impacts on renewable energy. The interaction of income and employment show that along with the income increases, the impacts of employment on renewable energy decrease. Our findings are helpful for government to figure out the determinants for rising the renewable energy generation, and take efficient measures to promote its development.